Biotic and Abiotic Components of The River - Annpoorna Sharma,; Dr. Manoj Singh, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This study offers a comprehensive analysis of the physico-chemical parameters of the Sarodha Dam in Kabirdham, Chhattisgarh, over three distinct periods: pre-autumn, autumn, and post-autumn of 2007. Key parameters examined include temperature, velocity, total solids, total suspended solids, total dissolved solids, turbidity, pH levels, dissolved oxygen content, free CO2 concentration, biochemical oxygen demand (BOD), chemical oxygen demand (COD), alkalinity, chlorides, sulphate levels, and fish species identification. The research identified 36 distinct fish species within the dam, underscoring the biodiversity present. Historically, water has been a crucial resource for human survival and development, with rivers playing a vital role globally. However, pollution from sewage and industrial effluents threatens these vital water bodies, leading to significant environmental and health issues. Despite advances in water treatment, urban piped water often remains contaminated, resulting in waterborne diseases such as jaundice, cholera, typhoid, and gastroenteritis. Pollution impacts rivers through chemical degradation and disruption of ecosystems, highlighting the need for interdisciplinary approaches to monitor and manage water quality effectively.
Keywords: Dissolved Oxygen; Turbidity; pH Levels; Seasonal Variations; Water Resource Management; Ecological Health